TARI NHAY LARA RUDA: SEBUAH REFLEKSI HUMANISME PEREMPUAN TIONGHOA MUSLIM - Latifah, Salsabila Alfi; Pramutomo, R.M. (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
This study explores the creative process behind the Nhay Lara Ruda dance by Salsabila Alfi Latifah, focusing on six fundamental components: (1) source materials, (2) personnel, (3) facilities, (4) tools and equipment, (5) influencing factors, and (6) creative considerations. The analysis of the dance form is divided into two key aspects: (a) the physical form—comprising elements that are perceptible through the five senses, such as movement, music, props, and floor patterns; and (b) the expressive form—which encompasses aesthetic and symbolic meanings. This analytical framework is informed by Rustopo’s perspective, as cited in Sejarah Tari Gambyong: Seni Rakyat menuju Istana, which conceptualizes artistic form as the embodiment of an artist’s internal experiences, made manifest through tangible media. It emphasizes the dynamic interplay between form (wadah) and content (isi). The notion of garap (creative composition) follows Rahayu Supanggah’s theoretical model, which underscores the synthesis of technical execution and artistic intuition. Employing a qualitative research methodology, the study utilizes a combination of performance analysis, literature review, in-depth interviews with selected informants, and direct observation of the Nhay Lara Ruda choreography. The findings indicate that the dance originates from an aesthetic vision and symbolically portrays the character and life journey of Nhay Lara Ruda. The work serves not only as a form of artistic entertainment but also as a symbolic narrative of perseverance and the human pursuit of happiness.